Roles of blue light and NADPH-dependent Thioredoxin Reductase C for the regulation of guard cell and sink leaf metabolisms - Bahadar, Humaira (2024)
The primary metabolism is essential for plant acclimation to diverse environment conditions and involves intricate networks of biochemical pathways and regulatory mechanisms. The complexity of plant metabolism is further enhanced by the compartmentalization within plant cells and by the fact that the primary metabolism ranges substantially among cell, tissue and organ types as well as because it is highly responsive to environmental conditions, such as light and stress conditions. Recent evidence suggests that the NADPH-dependent thioredoxin reductase C (NTRC) is important for the regulation of sink leaf metabolism as well as that starch breakdown is important during the blue light (BL)-induced stomatal opening. However, the underlying mechanisms behind these responses remain unclear. Taking this into account, this PhD thesis was performed to investigate (i) the effect of the lack of the NTRC on the regulation of source and sink Arabidopsis leaf metabolism under water deficit (WD) and (ii) the role of BL for the regulation of guard cell metabolism in tobacco and cowpea. Our findings collectively demonstrated that mild WD worsens the deleterious impacts of the NTRC deficiency in Arabidopsis sink leaves, which was associated to an increased lipid peroxidation, decreased catalase activity, decreased biomass accumulation over time and stronger metabolic alterations in in sink rather than source ntrc leaves. We further showed that the BL-induced stomatal opening is associated to changes in primary metabolism but not to starch degradation in both cowpea and tobacco guard cells. This thesis provides important information that improve our understanding on the regulation of plant metabolism in its diverse modules, from source to sink leaves and within guard cells, highlighting that the regulation of plant metabolism is species-specific and time and scale- dependent.